Comparing the Effectiveness of Cognitive-Behavioral Therapy with Schema Therapy on Communication Skills in Women Affected by Marital Infidelity - Hajjabari, Sanam; Boostan, Afsaneh; Hashemian, Kianoosh (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The present study was conducted with the aim of comparing the effectiveness of Cognitive-Behavioral Therapy with Schema Therapy on communication skills in women affected by marital infidelity.Materials and Methods: The research method was quasi-experimental with a pre-test, post-test and follow-up plan with a control group. The statistical population of this research was all the women involved with the issue of marital infidelity of their husbands who referred to the counseling centers of Tehran in 2022, who declared their readiness to attend the treatment plan at the call of the researcher in order to solve their problem. In this case, 45 subjects were selected by purposeful sampling and randomly replaced in three equal groups of 15 people (two experimental groups and one control group). To collect data, Queendom communication skills questionnaire (2004) was used. SPSS software and multivariate covariance analysis tests were used for data analysis.Findings: The results showed that both the intervention of Schema Therapy and Cognitive-Behavioral Therapy have created a significant difference in the post-test and follow-up phase in the variable of communication skills in women affected by marital infidelity compared to the control group (P0.05). Specifically, the Cognitive-Behavioral Therapy experimental group showed an increase of 4.85 points at the post-test stage and 5.05 points at the follow-up stage in communication skills compared to the Schema Therapy experimental group.Conclusion: Considering the findings of the current research, it can be recommended to mental health professionals and individuals active in couple therapy to enhance the mental health of women affected by marital infidelity by designing and applying appropriate methods inspired by Schema Therapy and Cognitive-Behavioral Therapy.